Effect of Fat Mass Localization on Fat Oxidation During Endurance Exercise in Women - Isacco, Laurie; Ennequin, Gaël; Boisseau, Nathalie (Frontiers in Physiology, 2020)
Independently of the total body fat mass, predominant upper body fat mass distribution is strongly associated with cardio-metabolic comorbidities. However, the mechanisms underlying fat mass localization are not fully understood. Although a large body of evidence indicates sex-specific fat mass distribution, women are still excluded from many studies and the specificities of the female population have been investigated only in few studies. Moreover, endurance exercise is effective for improving fat oxidation, suggesting that regular endurance exercise could participate in the management of body composition and metabolic health. However, no firm conclusion has been reached on the effect of fat mass localization on fat oxidation during endurance exercise. According to the available literature, this review aims to determine the effect of fat mass localization on fat oxidation rate during endurance exercise in women, and to identify future research directions to advance our understanding on women’s specificities. Despite a relatively limited level of evidence, the analysed studies indicate that fat oxidation during endurance exercise is higher in women with lower upper-to-lower-body fat mass ratio than in women with higher upper-to-lower-body fat mass ratio. Interestingly, obesity may blunt the specific effect of upper and lower body fat mass distribution on fat oxidation observed in women with normal weight during endurance exercise. Understanding women specificities is essential to develop appropriate physical activity strategies and ultimately to improve the prevention and treatment of cardio-metabolic diseases.